2015
DOI: 10.1111/apm.12465
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility among Staphylococcus epidermidis isolated from prosthetic joint infections, with focus on doxycycline

Abstract: In recent years, coagulase-negative staphylococci such as Staphylococcus epidermidis have gained importance as nosocomial pathogens, especially in immunocompromised patients and prosthetic joint infections (PJIs). These infections are often long lasting and difficult to treat due to the production of bacterial biofilm and the transformation of the bacteria into a stationary growth phase. Rifampicin is able to penetrate the biofilm, but to reduce the risk of development of rifampicin resistance it should be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…We found 30.2% S. epidermidis strains resistant to rifampicin, which is comparable with results of previous studies [17], where strains showed between 30% and 39% resistance [20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found 30.2% S. epidermidis strains resistant to rifampicin, which is comparable with results of previous studies [17], where strains showed between 30% and 39% resistance [20].…”
Section: Discussionsupporting
confidence: 92%
“…These discordant results could be explained by a large proportion of SE in previous studies on CNS PJIs. No CNS strain was resistant to linezolid or daptomycin, as described in previous studies [20]. Linezolid resistance was identified as the most frequent mechanism in CNS due to a mutation in 23S rDNA [21] in rare studies.…”
Section: Discussionmentioning
confidence: 94%
“…Doxycycline is an antibiotic widely used to treat bacterial infections 2123 . Numerous studies have reported that doxycycline exhibits anti-tumour and pro-apoptotic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus epidermidis has emerged as one of the most critical opportunistic pathogens of nosocomial infections in recent years because of the increase in frequency of invasive procedures ( Vuong et al, 2003 ; Chessa et al, 2015 ). The main pathogenicity associated with S. epidermidis involves the formation of biofilms on implanted medical devices ( Rupp, 2014 ; Hamad et al, 2015 ). The presence of the bacteria in biofilms drastically reduces the efficacy of conventional antibiotics and the host immune system, and this leads to persistent or recurrent infections ( Wolcott et al, 2010 ; Romling and Balsalobre, 2012 ).…”
Section: Discussionmentioning
confidence: 99%